From the doctrine of race to separatism in Catalonia: some reflections - Hermida del Llano, Cristina (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
In this paper, the author engages the debate concerning the right to decide, specifically concerning whether the referendum on the future of Catalonia can be prohibited within the Spanish Constitution. It is maintained that the answer is yes, given the principle of indissolubility (art. 2.1 of the Spanish Constitution) and of national sovereignty (art. 1.2. of the Spanish Constitution), while still affirming the principles that characterize Spain as a liberal democracy (arts. 1.1, 23.1, 9, and 10 of the Spanish Constitution). The article of Josep M. Vilajosana, entitled “Democracy and the right to decide” (2020) serves as the basis for the debate on this question. The argument here concerns how the evolutionary interpretation of democratic rights tied to a succinct conception of democracy does not justify the possibility of holding a referendum on the independence of Catalonia, and that, moreover, such a question cannot be decided unilaterally by the Catalan people. Here I highlight how the conscience of the Catalan race has served as motor to increase the secessionist fervor, which has unleashed, in addition to a legal dispute, a war of feelings and emotions.